Strategi Kepala Madrasah dalam Pelaksanaan Merdeka Belajar Di MTs Negeri 2 Musi Banyuasin - Mardianah, Mardianah (Yayasan Sembilan Pemuda Indonesia, 2021)
The purpose of this study is to examine the Madrasah Head's leadership style at MTs Negara 2 Musi Banyuasin. The research was conducted using a qualitative approach. Interviews, observation, and documentation were used to collect data. The education curriculum, madrasah management, institutional organization, financing of facilities and infrastructure, educators and education staff, administration, students, and residents around the madrasah were found to be supporting factors in improving the Independent Learning program in madrasah. The madrasah will function well if all of these factors are in place and operating in accordance with existing regulations. A more suitable environment will be created, and the quality of education in madrasah will improve. As a result, the madrasah principle plays a crucial role, as the quality of a madrasah will be reflected in the policies followed by the madrasah principal.